Enhanced hydrogen chemisorption and spillover on non-metallic nickel subnanoclusters. Issue 26 (15th June 2018) - Nishihara, Hirotomo; Ohtake, Fumihide; Castro-Muñiz, Alberto; Itoi, Hiroyuki; Ito, Masashi; Hayasaka, Yuuichiroh; Maruyama, Jun; Kondo, Junko N.; Osuga, Ryota; Kyotani, Takashi
Abstract : Thermal decomposition of nickelocene loaded onto zeolite-templated carbon (ZTC) yields very fine Ni nanoparticles including subnanoclusters which are in a unique oxidized state and exhibit high activity to H2 chemisorption and the following spillover under ambient conditions. Abstract : Very fine Ni nanoparticles including subnanoclusters are dispersed in zeolite-templated carbon (ZTC), by thermal decomposition (573 K) of nickelocene pre-loaded on ZTC which functions as a high-surface area support. X-ray absorption fine structure reveals that the Ni species formed by the thermal decomposition is in a unique oxidized state. It is different from nickelocene, Ni metal, or any other inorganic Ni species. The unique Ni species can dissociatively adsorb H2, and enhance the following spillover even under ambient conditions. The spillover activity of the non-metallic Ni subnanoclusters is superior to that of Ni-metal nanoparticles and even comparable to that of Pt nanoparticles.